DAMPAK MEDIA SOSIAL DALAM FENOMENA NYAMBAT OLEH WIRASWARA (ALOK) SUNDA PADA KILININGAN WAYANG GOLEK - Meilani, Dewi Wulan (Paraguna, 2022)
The presence of social media as a communication tool for people in urban and rural areas has an impact on traditional culture in Indonesia. There is an interesting phenomenon about traditional music in the commercial sphere in the West Java community in particular. This phenomenon is commonly referred to as nyambat. The emergence of this phenomenon usually occurs in arts that invite large audiences, such as wayang golek and kiliningan. Interestingly, this phenomenon can be a selling point for an entrepreneur or alok. This study uses a qualitative method with a number of data obtained through observation, interviews and documentation techniques with an ethnographic approach. Through this article, researchers will discuss the phenomenon of nyambat wiraswara in wayang golek performances, kiliningan and the impact of social media on this phenomenon.